Application of a weight gain curve for pregnant women - Siqueira, Arnaldo Augusto Franco de; Ciari Junior, Cyro; Mattos, Iara Lucia Brayner; Buralli, Keiko Ogura; Baptista Filho, Malaquias; Schor, Néia; Almeida, Pedro Augusto Marcondes de; Tanaka, Ana Cristina d'Andretta (Revista de Saúde Pública, 1977)
The authors studied the influence of maternal nutrition on birth weight using anthropometric techniques because these methods are of low cost, and do not need specialized manpower for their application. In the 460 pregnant women attended at a prenatal care service, there was a positive relationship between pre-gestational weight gain during pregnancy, birth weight and gestational age. Babies born from mothers with adequate pre-gestational weight were 296.7 grammes heavier than those of women with insufficient weight. Anthropometric curves for the measurement of maternal weight have been simplified and now this new curve is being tested.